Postural education as strategy for health promotion at school (Research, Society and Development, 2020)
Health promotion in the school context is a constant concern, since the school presents itself as a reference place for the acquisition of concepts and behaviors necessary for good self-care practices in health. Thus, this research aimed to evaluate the effects of a health promotion intervention, through postural education, aimed at elementary school students. The research was developed with students of the 6th grade of a municipal school in southern Brazil, and it took place in four stages: I) application of the initial questionnaire (pre-test) to verify the presence of musculoskeletal pain complaints and the students knowledge about adequate postural habits; II) theoretical-practical interventions focused on postural education; III) anthropometric data collection, backpack weighing and calculation of Body Mass Index (BMI); and IV) reapplication of the initial questionnaire (posttest). The data collected were tabulated and expressed as mean and frequency or analyzed using the Wilcoxon test. 32 students participated. The results indicated that all participants had pain complaints in various daily situations. Regarding the weight of the backpack, five students presented backpacks weighing more than 10% of body weight. Regarding the proper postural habits, it was observed that the student's correct response rate increased significantly after the postural education intervention. It is concluded that the action developed contributed to the students to broaden their knowledge and provided subsidies for them to adopt positive attitudes to minimize the risk of musculoskeletal injuries and postural changes.